The Effect of Socialization Implementation of Hazard Analysis And Critical Control Points (HACCP) on Food Processing in Bahteramas General Hospital and Kendari City General Hospital, Southeast Sulawesi Province - Reslin tobigo; Ellyani Abadi (KLASICS, 2022)
Food is a basic need for humans, food that is not safe for consumption can cause disease in humans, nosocomial infections, and food poisoning. The results of observations at the Bahteramas General Hospital and hospitals. The city of Kendari has not yet implemented the HACCP system, so innovation is needed so that the HACCP program can be implemented. The purpose of this study was to determine the effect of socialization on the application of food processing at Bahteramas General Hospital and hospitals. Kendari City. This type of research is quantitative, Quasy experiment design. The research was conducted at Bahteramas General Hospital, Southeast Sulawesi Province and in hospitals. Kendari City on January 28 - March 4, 2022. The sample is part of the nutrition staff, hosts and waiters at Bahteramas General Hospital and in hospitals. Kendari City in 2022. The intervention sample was given socialization about HACCP as many as 25 people obtained by simple random sampling and the control sample was not given socialization as many as 19 people obtained from the total sampling. Data collection techniques with questionnaires and observation. Data were analyzed using Mc.Neymar test. The results of research at the Bahteramas General Hospital obtained p value 0.031 < 0.05 for food processing obtained, and p value 0.031 < 0.05 for food presentation The conclusion is that there is an effect of socializing the application of HACCP on food processing and serving in hospitals. Kendari City. Suggestions for hospitals to implement the HACCP system. For health workers, food handlers and food servicers, to improve food management efforts based on the principles of food hygiene and sanitation.